Dynamic working bridge program to Japan 18th – 24th September 2023 / Mohd Faisal Abdul Wahab … [et al.] - Abdul Wahab, Mohd Faisal; Azmi, Azila; Tahir, Mohd Subri; Abdullah, Azrul; Mat Isa, Norshamshina (UiTM Global @ Office of International Affairs, 2024)
The esteem delegation of UiTM, which included Associate Professor Dr. Azila Azmi as team leader, Dr. Mohd Subri Tahir and Mr. Mohd Faisal Abdul Wahab (UiTM Pulau Pinang Branch), Associate Professor Dr. Azrul Abdullah and Mdm Norshamshina Mat Isa (UiTM Perlis Branch) and Mr. Muhammad Azmir Ishak, a representative of the Implementation Coordination Unit (ICU), embarked on a transformative journey to Japan through the Dynamic Working Bridge programme from 18 until 24 September 2024. This exploration of Japan's tourism sector and engagement with local operators catering to Muslim tourists showcased the programme’s dedication to fostering significant relationships and connections between two distinct cultures.